2015
DOI: 10.1515/pjvs-2015-0072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytogenics on growth performance, fecal score, blood profiles, fecal noxious gas emission, digestibility, and intestinal morphology of weanling pigs challenged with Escherichia coli K88

Abstract: Phytogenic feed additives have become attractive alternatives for use in animal diets. The objective of the present study was to evaluate the effect of a phytogenic-based feed additive on growth performance, nutrient digestibility, blood profiles, fecal noxious gas emission, and intestinal morphology of weaning pigs after dietary challenge with E. coli K88. A total of 120 crossbred pigs [(Yorkshire × Landrace) × Duroc)] with an initial body weight (BW) of 6.09 ± 0.96 kg (21 d of age) were assigned randomly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…(2008) showed improved weight gain of nursery pigs supplied with allicin as the functional component in aged garlic extract. Devi et al. (2015) showed that improved weight gain and apparent total tract digestibility of ash in pigs by feeding phytogenic additive combination (clove, cinnamon, and fenugreek) after dietary challenge with F4 + ETEC.…”
Section: Applications Of Preventing Postweaning Diarrhea Associated Wmentioning
confidence: 99%
“…(2008) showed improved weight gain of nursery pigs supplied with allicin as the functional component in aged garlic extract. Devi et al. (2015) showed that improved weight gain and apparent total tract digestibility of ash in pigs by feeding phytogenic additive combination (clove, cinnamon, and fenugreek) after dietary challenge with F4 + ETEC.…”
Section: Applications Of Preventing Postweaning Diarrhea Associated Wmentioning
confidence: 99%
“…Oral challenge with ETEC has been used widely as model for post-weaning diarrhea (PWD) ( Wellock et al, 2009 ) and has often been used in pig feeding trials to assess the ability of a diet to reduce the infection or its consequences ( Bosi et al, 2004a , b). Dietary phytogenics could be used to replace antibiotic growth promoters (AGP) in the diets of weaning pigs for significantly improving the average daily gain (ADG) without any negative effects on growth performance under challenge with E.coli K88 compared with AGP and organic acids ( Mohana Devi et al, 2015 ).…”
Section: Disease Challenge Modelsmentioning
confidence: 99%
“…Therefore, alternative strategies have been actively investigated to replace these synthetic antimicrobial agents. Many studies have been published about different additives’ effects on broiler chicken performance and immune response when challenged with Escherichia coli K88, such as prebiotics, probiotic, short-chain fatty acids, and essential oils, but little is known about polysaccharide additives [4,5,6,7]. These additives promote growth performance by increasing the average daily feed intake and improving immune function and intestinal villi development, but there has been very little research on the effects on the intestinal microbial community structure and balance of the host [8,9].…”
Section: Introductionmentioning
confidence: 99%